2021
DOI: 10.1097/dbp.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Developmental Disorder Diagnoses of Foster and Nonfoster Children Enrolled in Medicaid

Abstract: Objective: This study used Medicaid claims to compare the prevalence of mental health disorders (MHDs) and developmental disorders (DDs) between foster and nonfoster youth. Methods: Medicaid claims data were used to identify MHDs and DDs. Diagnosis codes were categorized into 16 MHD and 8 DD groups.Children were enrolled in their respective Medicaid plan for at least 30 days and had at least 1 health care encounter generating a claim. Prevalence was compared between children in foster care and children not in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…They found a prevalence of hearing impairment (3.8%), epilepsy (1.2%), visual impairments (11.2%), and ADHD (6.2%), but they did not describe the prevalence of more specific impairments, and they had a much smaller sample size. Keefe et al (2022) 17 reviewed Medicaid claims data across many pediatric practices in the Houston area and found that 21.0% of children in foster care had a developmental disorder diagnosis. This prevalence is lower than in our clinic, which could be due to our clinic exclusively serving children in foster care or due to more rigorous surveillance and screening in our clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a prevalence of hearing impairment (3.8%), epilepsy (1.2%), visual impairments (11.2%), and ADHD (6.2%), but they did not describe the prevalence of more specific impairments, and they had a much smaller sample size. Keefe et al (2022) 17 reviewed Medicaid claims data across many pediatric practices in the Houston area and found that 21.0% of children in foster care had a developmental disorder diagnosis. This prevalence is lower than in our clinic, which could be due to our clinic exclusively serving children in foster care or due to more rigorous surveillance and screening in our clinic.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Reported health conditions that may be more common in children in foster care compared with the general population include hearing problems (4% vs ,1%), 4,9,10 vision problems (3.4%-11% vs 1.5%-5.7%), 4,[11][12][13] neurologic and developmental problems or delays (25%-33.8% vs 6%-17%), 3,[13][14][15][16] and speech delays (11% vs 5%). 4 Previous research often relied on national surveys based primarily on caregiver reports, 4 Medicaid claims records, 17,18 and data from referral and assessment centers for children initially entering foster care, 3 but there are few data about medically diagnosed audiologic, developmental, neurologic, and ophthalmologic conditions in children in foster care in a primary care setting. Data from a primary care setting that follow the medical home model may be particularly useful because of the model's emphasis on continuity of care and comprehensive medical care for children in foster care.…”
mentioning
confidence: 99%
“…Children in foster care are a uniquely vulnerable population with increased mental health needs due to very high rates of complex trauma that arises from adverse childhood experiences both prior to and during foster care. (Keefe et al 2022) From previous research we know that this youth are vulnerable in many ways, and at extra risk of continued or later marginalization. (Bakketeig and Backe-Hansen 2008, p. 18…”
Section: Pre-described Vulnerability On a Heterogenous Populationmentioning
confidence: 99%
“…The most commonly diagnosed conditions among foster youth are attention deficit/hyperactivity disorder (ADHD), bipolar disorder, communication disorder, and depressive disorders ( 5 ). Treatments for these commonly encountered disorders may include psychotropic medication in conjunction with other therapies, and indications for psychotropic medication use vary by diagnosis and severity of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Nationally, there is a growing number of children requiring mental health services (1). Within the pediatric population, several state-based studies found that children in the foster care system are more likely to have a mental health diagnosis, higher mental health needs, and higher rates of psychotropic use (2)(3)(4)(5). Furthermore, psychotropic medication use in pediatric populations has significantly increased over the past decade, especially off-label use of atypical antipsychotic medications (6,7).…”
Section: Introductionmentioning
confidence: 99%